Overtemperature protection systems for spallation target in China initiative accelerator driven sub-critical system. (June 2019) - Cui, Wenjuan; He, Zhiyong; Ma, Wenjing; Yin, Kai; Zhao, Qiang; Zhang, Xueying; Chen, Zhiqiang
Highlights: An over-temperature protection system has been designed for the spallation target in CiADS system to prevent the granular target from abnormal irradiation by the accelerator's beam. In order to evaluate the validity of the protection functions, the spatio-temporal variations of the target temperatures have been investigated with the heat transfer model. The simulation results can be summarized as follows. (1) Beam scanning can be used to avoid very high temperature at the target center. (2) The granular blockage can also be detected by measuring the temperatures in the four directions. (3) Beam deviation can be detected by comparing the temperatures in the four directions. Finally, over-temperature protection logic was designed, the accelerator and reactor in CiADS are shut down urgently by removing power from the ECR ion source, allowing the accelerator to urgently shut down its beam. Abstract: In an accelerator driven sub-critical system (ADS), a spallation target is irradiated by high-power proton beam to drive a sub-critical reactor. To continuously produce very intense neutrons, it is very important to prevent the unsafe operation of the target. This paper reports an over-temperature protection system for the spallation target in China initiative ADS system, where tungsten granules in the target container are used as both coolant and target materials. In order to protect the target from abnormal irradiation by the accelerator's beam when the granules are blocked or when the beam deviates from the target center, 12 sets of thermocouples are mounted inside the target container to monitor the target temperature. To evaluate the protection functions of these thermocouples, the heat transfer model of particles has been employed to investigate the spatio-temporal variations of the target temperatures when tungsten granules stay static in the target. The simulation results indicate that the temperatures of the thermocouples increase with the irradiation time and the granular blockage can be detected by analyzing the temperatures of these thermocouples. On the other hand, when the beam center deviates from the target center, the azimuthal distribution of the target temperature becomes non-uniform, and the temperature of the thermocouple close to the beam center increases faster. Finally, in the monitoring system for the over-temperature protection, 12 thermocouples divided into 3 groups which are fixed within the target in the upper, central and lower parts of the target, and 4 thermocouples in each group are located in four directions of east, south, west, and north. If two or more channels of four directions in one group exceed the set point, the protective function of granular blockage will be initiated; if two or more channels in one direction are greater than the set point, the protective function of beam deviation will be triggered.